Templated assembly of a µ6-CO32- dodecanuclear lanthanum dibenzoylmethanide hydroxido cluster with concomitant formation of phenylglyoxylate - Andrews, P.; Beck, T.; Forsyth, C.; Fraser, B.; Junk, P.; Massi, Massimiliano; Roesky, P. (The Royal Society of Chemistry, 2007)
Reaction of LaCl3 and dibenzoylmethane (Ph(2)acacH) in methanol with an excess of triethylamine resulted in the unexpected formation of a dodecanuclear hydroxo-bridged La cluster templated by CO32- and phenylglyoxylate (Phgly), as determined by X-ray crystallography.